2018
DOI: 10.1016/j.ekir.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathological Significance of Autoantibodies to Erythropoietin Receptor in Type 2 Diabetic Patients With CKD

Abstract: IntroductionWe examined the impact of autoantibodies on the erythropoietin receptor (EPOR) in type 2 diabetic patients with chronic kidney disease (CKD).MethodsA total of 112 Japanese patients with type 2 diabetes who had CKD were enrolled in this study and followed for a mean of 45 months. Sera from these patients were screened for anti-EPOR antibodies using enzyme-linked immunosorbent assays.ResultsAnti-EPOR antibodies were detected in 26 patients (23%). Anti-EPOR antibodies were associated with low hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
(53 reference statements)
1
19
3
Order By: Relevance
“…We have previously reported using a homogenous Japanese cohort with DKD (mean eGFR was 42 ml/min/1.73 m 2 and mean urinary protein was 2.7 g/day) that elevated anti-EPOR antibodies levels carried the highest risk of ESKD compared to those with undetectable or low anti-EPOR antibodies levels (hazard ratio 2.78 [95% CI 1.20, 6.43]). 10 We validated these findings in the current study using a more diverse cohort of the ADVANCE trial cohort that consists of individuals with earlier stages of DKD (mean eGFR J o u r n a l P r e -p r o o f was 74 ml/min/1.73 m 2 and median UACR was 15 mg/g). Our findings further suggest that anti-EPOR antibodies can be a useful circulating biomarker for predicting the risk of kidney disease progression even in earlier stages of DKD.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…We have previously reported using a homogenous Japanese cohort with DKD (mean eGFR was 42 ml/min/1.73 m 2 and mean urinary protein was 2.7 g/day) that elevated anti-EPOR antibodies levels carried the highest risk of ESKD compared to those with undetectable or low anti-EPOR antibodies levels (hazard ratio 2.78 [95% CI 1.20, 6.43]). 10 We validated these findings in the current study using a more diverse cohort of the ADVANCE trial cohort that consists of individuals with earlier stages of DKD (mean eGFR J o u r n a l P r e -p r o o f was 74 ml/min/1.73 m 2 and median UACR was 15 mg/g). Our findings further suggest that anti-EPOR antibodies can be a useful circulating biomarker for predicting the risk of kidney disease progression even in earlier stages of DKD.…”
Section: Discussionsupporting
confidence: 55%
“…This may explain the clinical observation that individuals with diabetes mellitus are more likely to be anaemic than individuals without. 5,6 We also found that anti-EPOR antibodies upregulated the expression of monocyte chemoattractant protein-1 (MCP-1) mRNA on human tubular epithelial cells under high glucose conditions, 10 suggesting a mechanistic link of anti-EPOR antibodies with the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Recently, anti-erythropoietin receptor (EPOR) antibodies have been reported to be pathologically associated with renal interstitial inflammation in type 2 diabetic patients. Furthermore, autoantibodies to EPOR may be involved in disease progression and are a useful serologic marker for the progression of kidney dysfunction in type 2 diabetic patients with CKD (22,23). These biomarkers may be clinically useful and valuable.…”
Section: Biomarkers For Pathological Changes and Outcome Predictionmentioning
confidence: 99%